(untitled) (Journal of Green Business School, 2025)
This research examines the influencing factors of Bangladeshi students’ selection of private tertiary educational institutions for Bachelor of Business Studies (BBA) degrees. It employed a qualitative study design. Twenty-one students from different universities were chosen using a purposive sampling technique for three Focus Group Discussions (FGD). A thematic analysis identified common themes and patterns in the responses. It has been found that the institutional reputation and accreditations, the price of a degree, peer and family influence, geographical proximity, infrastructure and resources, and open field and greenery are the most crucial elements that influence the enrolment choice in a university. This research comprehensively explores various influencing elements of business undergraduate students’ preferences for private universities in Bangladesh. It captures diverse perspectives through a qualitative approach and purposive sampling. The finding of this research contributes valuable insights for the universities’ policymakers and educators of other levels of education. J. of Green Business. Sch. Vol 6(1), Jan-Dec, 2023; pp 19-30